Analisa Orientasi Pelayanan Melalui Semangat Tim Dalam Upaya Meningkatkan Kepuasan Konsumen Menggunakan Model SERV*OR (Studi Kasus Pada Perawat RSUD Abdul Wahab Sjahranie Samarinda) - Deasy Kartika Rahayu; Nadia Tri Handayani (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2017)
Service orientation is a part of organization’s climate. Service orientation defines as the set of organizational activities designed to create and deliver an excellent service. Service orientation is a strategic choice to create an excellent service. Service driven organization will give psychological benefits to employee such as team spirit (esprit de corps) and organizational commitment. Team spirit is important because the effectiveness and organization’s performance are depended on team work. Productivity and organization’s performance are influenced by commitment.The study was intended to identify the relationship between service orientation and team spirit (esprit de corps) and organizational commitment and also between team spirit (esprit de corps) and organizational commitment. This study was quantitative research using cross sectional design. The subjects of this study were nurses who work at RSUD Abdul Wahab Sjahranie Samarinda. The independent variable was service orientation which measured using SERV*OR. The dependent variables were team spirit (esprit de corps) and organizational commitment. The data were analysed using correlation and regression analysis.This study showed that there were significant positive relationship between service orientation and team spirit (esprit de corps) (r=+0,396, sig <0,05), between service orientation and organizational commitment (r = +0,432, sig <0,05), and between team spirit (esprit de corps) and organizational commitment (r = +0,538, sig <0,05). Employee empowerment gave the smallest contribution to team spirit and gave none contribution to organizational commitment among nurses at RSUD A.W.Sjahranie Samarinda.